The nature of transition circumstellar disks : I. The ophiuchus molecular cloud - Cieza, Lucas A. (2010)
We have obtained millimeter-wavelength photometry, high-resolution optical spectroscopy, and adaptive optics near-infrared imaging for a sample of 26 Spitzer-selected transition circumstellar disks. All of our targets are located in the Ophiuchus molecular cloud (d ∼ 125pc) and have spectral energy distributions (SEDs) suggesting the presence of inner opacity holes. We use these ground-based data to estimate the disk mass, multiplicity, and accretion rate for each object in our sample in order to investigate the mechanisms potentially responsible for their inner holes. We find that transition disks are a heterogeneous group of objects, with disk masses ranging from <0.6 to 40 MJUP and accretion rates ranging from <10-11 to 10 -7 M ⊙yr-1, but most tend to have much lower masses and accretion rates than "full disks" (i.e., disks without opacity holes). Eight of our targets have stellar companions: six of them are binaries and the other two are triple systems. In four cases, the stellar companions are close enough to suspect they are responsible for the inferred inner holes. We find that nine of our 26 targets have low disk mass (<2.5 MJUP) and negligible accretion (<10-11 M ⊙yr-1), and are thus consistent with photoevaporating (or photoevaporated) disks. Four of these nine non-accreting objects have fractional disk luminosities <10-3 and could already be in a debris disk stage. Seventeen of our transition disks are accreting. Thirteen of these accreting objects are consistent with grain growth. The remaining four accreting objects have SEDs suggesting the presence of sharp inner holes, and thus are excellent candidates for harboring giant planets.